Financing incremental abatement costs under asymmetric information - Carsten Schmidt (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1998)
The paper analyzes international environmental agreements that incorporate transfers from a group of industrialized countries to developing countries in a situation of asymmetric information. The framework of the analysis is a static model of transboundary pollution in which information on abatement costs is public, but information on abatement benefits is private. The properties of cooperative solutions for separating and pooling equilibria are analyzed. It is shown under which circumstances it is not optimal for the donors to compensate recipients for their net incremental abatement costs, but where instead it is profitable for both parties to apply the gross incremental cost concept. The paper discusses the implications of the results for projects to protect global environmental resources within the concept of 'joint implementation.
Keywords: D61; D62; H77; Q20; Q28; 330; international environmental agreements; asymmetric information; incremental abatement costs; side payments; joint implementation